KEMAMPUAN LULUSAN SEKOLAH TINGGI PARIWISATA AMPTA DALAM MENGHADAPI PERSAINGAN DI DUNIA KERJA - Jefry Angg, Risky Atwar; Larasati, Sri (Sekolah Tinggi Pariwisata AMPTA, 2018)
The purpose of this research is to know wtether knowledge, skill, responsiveness and communication skill influence in job competition for graduate student from Sekolah Tinggi Pariwisata AMPTA. The population in this study are student pf Sekolah Tinggi Pariwisata SMPTA that graduated in 2013 until 2016, the total population in this studt is 702 and 200 respondents who have worked taken as samples, samples were taken with non probability sampling technique and accidental sampling approach. Sampling approach using regression equations obtained results that through test results F (regression analysis jointly) may note that the value of F = 147.104 count with the significance of 0.000 < 0.05. The test results of the test F reinforced with testing the determination of the coefficient that shows the value of 74.6%) (0.746. From Test t (partially) can result in variable knowledge with a value of t = 3,173 and significance of the value 0002 < 0.05, variable skill with a value of t = 2,949 and value the significance of 0.004 < 0.05, variable attitude with a value of t = 2,688 and value the significance of 0.008 < 0.05, variable communication skill with a value of t = value and significance of 4,497 0000 < 0.05. From the above results can be known that the hypothesis posed was not proven in other words that all of these variables can be said to have a positive and significant effect simultaneously as well as partial toward the ability of STP graduates AMPTA in the face of competition in the world of work. Key words: skills, knowledge (knowledge), Skill (skill), Attitude (attitude), Communication Skills (ability to communicate), Sekolah Tinggi Graduates AMPTA.